DISTRIBUSI VERTIKAL BAKTERI DAN KAITANNYA DENGAN KONSENTRASI KLOROFIL-a DI PERAIRAN KALIMANTAN TIMUR - Nuchsin, Ruyitno (Makara Journal of Science, 2007)
Vertical distribution of bacteria population in relation to chlorophyll-a in East Kalimantan waters. Study on distribution of bacteria population and its relation to concentration of chlorophyll-a has been conducted in August – September 1999 in East Kalimantan waters. The purpose of the study was to observe the correlation between population of bacteria and concentration of chlorophyll-a in water column. Acridine Orange Epifluorescence Microscopy method was used to analyze bacteria population, while fluorometric method was used to determine chlorophyll-a concentration. The result of the study showed that bacteria population was positively correlated to chlorophyll-a concentration, area with high bacteria population has high concentration of chlorophyll-a. The high bacteria population was found in the water columnh of the 25 m deep,as well as for chlorophyll-a concentration, ranged between (4 and 90) x 106 cell per ml and (0.2 and 1.14) mg per m3 respectively. It was concluded that vertical distribution of bacteria population was closely correlated to the concentration of chlorophyll-a